Internet-Based Development of Medicinal Plants Geospatial System in Phu Phan Forest Complex: Northeastern Thailand - Chantraket, Rutchanee; Uttaruk, Pornchai; Klinhom, Usa; Skole, David L.; Samek, Jay H.; Castaneda, Oscar (Agriculture and Natural Resources, 2014)
This new work developed tools for the management and protection of medicinal plants or herbs in their native habitat in the Phu Phan forest complex, northeastern Thailand. The biological diversity of medical plants was analyzed as well as their distribution and status, and a geoinformatics database was developed including distribution maps to be used for the management of medicinal plants in the Phu Phan forest complex, based on the Local Biodiversity Survey and Data Collection Project conducted by the Ministry of Natural Resources and Environment from July 2006 to January 2009. The 49 permanent sampling plots were established in four provinces. The survey data were used to develop a database for plant management and the ArcGIS 10 Desktop and ArcGIS 10 for Server software packages developed by ESRI were used to develop the geoinformatics database. As a result, the Internet-based Geoinformatics Database of Thai Medicinal Plants has been established as a reference center covering 429 medicinal plant species belonging to 102 families. Of these species, 50 were in the family Leguminosae and Shorea obtusa Wall. ex Blume was the most dominant species with the highest importance value index. The Shannon-Wiener species index, species diversity index and evenness index were 3.8377, 46.42 and 0.7390, respectively, with 16 species classified on the International Union for Conservation of Nature Red List of Threatened Species. The geospatial database consisted of 32 layers of basic, environmental and survey data, which can be accessed via the Internet to search for large trees and medicinal plants. The database details of plants include scientific names, common names, local names, morphological characteristics, ethno-medicinal properties, other uses, references, images and distribution maps. The results of this study can be used as basic information and as a model for developing other tools for further planning and management of medicinal plants including their habitat in other regions of Thailand.